REFORMULASI HUBUNGAN AGAMA DENGAN NEGARA: Dialog Pemikiran Yusuf al-Qardhawy dengan Ulama Klasik tentang Politik Kenegaraan dan Implikasinya bagi Perpolitikan di Indonesia - hudi, Mashudi (IAIN Walisongo Semarang, 2014)
This research describes the formulation want state politics and religious ties withthe country according to Yusuf al-Ulama Qardhawy and Classical. The results ofthe analysis of their thinking as outlined in his works, can be explained that Yusufal-Qardhawy reformulate the concept of the relationship between religion and thestate as well as the state political through and istiab syumuli method, a problem ofhow to resolve the impasse in state politics as well as the relationship betweenreligion and state product classical scholars thought. Reformulation of the conceptof the relationship between religion and the state is the solution to the stagnation(stagnation) patterns of thought classical scholars. The concept of state politics byYusuf al-Ulama Classical Qardhawy and there are points in common with theIndonesian state politics in the context of the present though not totally, so thatsome can be implemented to control the practice of politics in Indonesia latelyaway from religious ethics.***Penelitian ini ingin menjelaskan formulasi politik kenegaraan dan hubunganagama dengan negara menurut Yusuf al-Qardhawy dan Ulama Klasik. Hasilanalisis dari pemikiran mereka yang dituangkan dalam karya-karyanya, dapatdijelaskan bahwa Yusuf al-Qardhawy mereformulasi konsep hubungan agamadan negara serta politik kenegaraan tersebut melalui metode shumulÄ« dan istiâab,suatu cara menyelesaikan kebuntuan problematika politik kenegaraan sertahubungan agama dan negara produk pemikiran ulama klasik. Reformulasi konsephubungan agama dan Negara tersebut merupakan solusi atas stagnasi (kejumudan)corak pemikiran ulama klasik. Secara teoritis, konsep politik kenegaraanmenurut Yusuf al-Qardhawy dan Ulama Klasik terdapat titik kesamaan denganpolitik kenegaraan Indonesia dalam konteks sekarang meskipun tidak secaratotal, sehingga sebagian dapat diimplementasikan untuk mengendalikan praktikperpolitikan di Indonesia yang akhir-akhir ini jauh dari etika agama.Keywords: reformulasi, agama, negara, politik kenegaraan